The relationship between place identity and community resilience: Evidence from local communities in Isfahan, Iran. (May 2023) - Sobhaninia, Saeideh; Amirzadeh, Melika; Lauria, Mickey; Sharifi, Ayyoob
Abstract: Today, many cities are experiencing many natural disasters and hazards due to climate change, particularly in the Global South. Environmental risks increase acute community vulnerabilities that worsen the effects of these hazards and make a recovery more difficult. However, community resilience can decrease people's vulnerabilities and improve their capacity to cope with and adapt to environmental hazards. It is assumed that place identity, as a cultural resource, can positively affect the resilience of communities. This exploratory survey research, thus, aims to understand the relationship between place identity and community resilience. Data is gathered using a questionnaire survey and analyzed using the principal component analysis. Case studies are two local communities in Isfahan, Iran, the Abbas Abad neighborhood and Barazandeh neighborhood, affected by the drying up of Zayandehrood River's aqueducts. The study results show a positive correlation between place identity and community resilience in the selected communities. The community with a stronger place identity tended to show stronger community resilience than the other. Therefore, it can be concluded that improving place identity might contribute to better community adaptation and recovery in times of slow-onset or sudden environmental disruptions. However, this relationship should not be considered a causal relationship. The present study highlights the role of place identity in community adaptive capacities and helps policymakers better plan to enhance community resilience. Policymakers can use the study's results to empower the communities facing slow-onset environmental disruptions. Highlights: Community resilience is essential for dealing with environmental hazards. We study the linkage between place identity and community resilience. The case studies are two communities in Iran with different characteristics. We find a positive correlation between place identity and community resilience. We propose frameworks for enhancement of place identity and community resilience.